Morphological and Genotypic Characterization of Fungi Associated with the Ascochyta Blight Complex in Western Regions of Algeria - Tadja, A. (European Scientific Journal, ESJ, 2018)
The study is conducted in two growing areas of garden pea (Pisum sativum L.) in northwestern Algeria. Damages caused by Ascochyta sp complex are important in particular for the variety of Kelvedon Wonder. Observations carried out on the infected plants for several years, indicate the presence of superimposed necrosis of different sizes on all aerial organs. However, these observations do not differentiate symptoms by species. The results of morphological and molecular characterization with sequencing in internal transcribed spacer (ITS) regions and inoculation tests on 32 isolates in the laboratory of symbiosis and plant pathology from Toulouse (France), show a reconciliation of the sequencing by polymerase chain reaction (PCR) products and size necrosis for all Ascochyta pinodes and pinodella. Alone, Ascochyta pisi is distinguished by a smaller size necrosis. On the molecular level, all isolates whose ITS regions were amplified by PCR, expresses similar size products (550 bp). This molecular weight is found on a large set of pathogenic fungi. The three species of Ascochyta sp complex do not exhibit polymorphism for Pisum sativum species and have an identical molecular weight. The pathogenicity tests performed showed differences in aggressiveness on the host plant. Ascochyta pinodes is the most aggressive than the other two species. As a result, it causes more damage to the crop.